Improvement of grid injected currents in single-phase inverters rejecting DC link voltage oscillations based on multi-resonant filtering - Guilherme M. Pelz; Sérgio A.O. da Silva; João A.C. Neves; Leonardo P. Sampaio (International Journal of Electrical Power & Energy Systems)
The operation of grid-tied single-phase inverters generates oscillations in its DC link voltage. If only active/reactive power is controlled by the inverter, this oscillation is at twice the grid frequency. In situations where the inverter output current and/or the grid voltage also has harmonic components, the DC link voltage becomes also polluted by oscillating components at even multiple frequencies of the grid voltage. Such oscillations are propagated through the DC link voltage control loop, increasing the THD index of grid current reference signal. To solve this drawback, this article proposes the insertion of a multi-resonant filter into the DC link voltage control loop, ensuring a harmonic free grid current reference signal. With the proposed filter and without any increase in the power circuit, the use of smaller capacitances in the DC link is allowed, since the DC link voltage oscillation does not interfere in the power quality indexes of the controlled current. A filter tuning methodology is presented to ensure that the design of each filter and of the DC link voltage controller is independent, relating the filter settling time and the system stability. At the same time, the use of the proposed filter allows the voltage controller to be tuned at higher frequencies, improving the DC link voltage dynamic response. The proposal is experimentally validated through a single-phase grid-tied double-stage photovoltaic (PV) system, that can also operate only as a parallel active power filter (PAPF) or, simultaneously as a multifunctional PAPF + PV system.